Hospitalized patients on orexin receptor antagonists have a lower risk of falls - Yukina Ohshima; Takuya Araki; Hideaki Yashima; Noriyuki Nakayama; Koujirou Yamamoto (Universitas Padjadjaran (Unpad), 2022)
Falls and fall-related injuries remain a major safety concern in many hospitals and nursing homes. Although many studies have examined the relationship between accidents and sedating medications, further analysis is needed of the association between falls and individual hypnotics. The aim of this study was to clarify the association between hypnotics and the risk of falls in hospital. The impact of hypnotics on fall events was retrospectively evaluated in patients aged 20 years or older who were admitted to Gunma University Hospital between January 2013 and March 2022. Logistic regression analysis was performed with age, sex, and drug prescription status as the independent variables and fall events as the dependent variable. Of the 54,019 patients included in the study, 1,460 experienced a fall during hospitalization (incidence, 2.7%). The hypnotics prescribed included orexin receptor antagonists, melatonin receptor agonists, and benzodiazepine receptor agonists. Logistic regression analysis showed that age (odds ratio [OR] 1.04), male sex (OR 1.14), estazolam (OR 2.99), flunitrazepam (OR 2.34), brotizolam (OR 1.65), diazepam (OR 3.34), lorazepam (OR 2.93), alprazolam (OR 1.91), ethyl loflazepate (OR 2.81), zolpidem (OR 1.40), eszopiclone (OR 1.87), clonazepam (OR 1.94), and ramelteon (OR 2.15) independently contributed to falls. Short-acting benzodiazepine receptor agonists tended to have smaller ORs for fall risk. Orexin receptor antagonists were not associated with falls. Therefore, orexin receptor antagonists and short-acting benzodiazepine receptor agonists are likely safer than intermediate-acting and long-acting benzodiazepines. Keywords: fall risk, hypnotics, acute care hospitals